Climate Change and Public Health: Analysis of the Increasing Burden of Vector Borne Diseases in Tropical Countries - Asnur Hi. Hukum (Journal of Public Health Indonesian, 2025)
Climate change is accelerating the transmission of vector borne diseases, particularly in tropical regions characterized by high temperatures, elevated humidity, and ecological conditions favorable for vector proliferation. This article examines the relationship between climate change and the rising burden of vector borne diseases such as dengue, malaria, chikungunya, and Zika through a Systematic Literature Review conducted in accordance with PRISMA guidelines. From 1,246 initially identified publications, 79 studies met inclusion criteria and were thematically synthesized. Findings indicate that increasing temperatures accelerate vector development and pathogen replication, rainfall variability expands breeding habitats, and high humidity prolongs vector survival. In tropical countries, rapid urbanization and infrastructural inequality further exacerbate disease risks, disproportionately affecting low income populations. The study highlights the need for climate informed early warning systems, innovative vector control methods, strengthened surveillance, and cross sector climate adaptation policies. These insights provide a scientific foundation for designing resilient public health strategies to address emerging vector borne disease threats in a warming climate